KONDISI PERPIPAAN AIR LIMBAH DOMESTIK STUDI KASUS DI DESA MEKARSARI: Condition Of Domestic Wastewater Pipelines Case Study In Mekarsari Village - Kaka, Yumensi; Aminullah, Aminullah; Dewi, Ni Made Nia Bunga Surya (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2025)
The purpose of this study was to determine the condition and system of domestic wastewater piping in Mekarsari Village. This type of research is a case study in Mekarsari Village related to the condition of the Wastewater Treatment Plant (IPAL). The results of the study indicate that the piping system uses a gravity system, a wastewater distribution system in Mekarsari Village that channels wastewater from higher areas to lower areas. This system is commonly used because it does not require additional energy. This end system uses a pipe network connected to the Wastewater Treatment Plant (IPAL) to treat wastewater before being reused. The condition of the domestic wastewater piping in Mekarsari Village is still in good or normal condition. Leaks or loss of discharge have not been found, this is because the pipes used are iron pipes.